Comparative estimation of crude protein, phenols and tannins concentration of Lotus corniculatus growing in different habitats - Giagourta P.; Parissi Z.M.; Kyriazopoulos A.P.; Abraham E.M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Lotus corniculatus is a temperate perennial legume that contains condensed tannins which increase the animal production and decrease bloating in ruminants. The aim of this study was to investigate differences in crude protein (CP), total phenols (TPH), total tannins (TT) and condensed tannins (CT) concentration of L. corniculatus individuals growing in oak forest and in open grasslands. The collection of plant material was conducted in Taxiarchis area, Chalkidiki, Northern Greece from four sites in an oak forest and four sites in adjacent open grasslands. Twenty individual plants of L. corniculatus were randomly collected at the flowering stage in summer 2011 from each of the eight sites and were analysed for CP, TPH, TT and CT concentration. According to the results, the CP concentration was significantly higher in individuals from the forest in comparison to individuals from the open grasslands. Inversely, the individuals from the open grasslands had significantly higher concentration of TPH, TT and CT compared to those from the forest.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)